Eremophilane-Type Sesquiterpenes from a Marine-Derived Fungus Penicillium Copticola with Antitumor and Neuroprotective Activities - Zhang, Jianping; Liu, Dong; Fan, Aili; Huang, Jian; Lin, Wenhan (Marine drugs, 2022)
Chemical examination of a marine sponge-associated Penicillium copticola fungus resulted in the isolation of ten undescribed eremophilanes, namely copteremophilanes A–J (1–10), along with two new glycosides, 5-glycopenostatin F (11) and 5-glucopenostatin I (12). Their structures were determined by extensive spectroscopic data, in association with ECD data and chemical conversions for configurational assignments. Analogs 1, 2, and 10 represent a group of uncommon skeletons of eremophilanes with an aromatic ring and a methyl migration from C-5 to C-9, and analogs 11 and 12 are characteristic of a PKS scaffold bearing a glucose unit. The incorporation of a chlorinated phenylacetic unit in 3–9 is rarely found in nature. Analog 7 showed neuroprotective effect, whereas 8 exhibited selective inhibition against human non-small cell lung cancer cells (A549). This study enriched the chemical diversity of eremophilanes and extended their bioactivities to neuroprotection.